<h2><u>
Solution</u>
:</h2>
<em>To find the zero,</em>
<em>x</em> + 1 - 4 = 0
<em>x</em> = 4 - 1
<em>x</em> = 3
3 is the <u>root</u> of <em>(x + 1) - 4</em>.
Answer:
Here for points
Step-by-step explanation:
Answer:
186.3
To find the answer you have to do inverse operations
9×20.7=186.3
186.3÷20.7=9
Cot = Cos/Sin
Cos = 12/13
Sin = 5/13
Therefore, 12/3 divided by 5/13 equals 12/5
Answer is 1.
Answer:
g(-8) = -23
Step-by-step explanation:
g(x) = 3x + 1 <em>Plug in g(-8)</em>
g(-8) = 3(-8) + 1 <em>Multiply 3 by -8</em>
g(-8) = -24 + 1 <em>Add 1 to -24</em>
g(-8) = -23